2009
DOI: 10.1002/ijc.24740
|View full text |Cite
|
Sign up to set email alerts
|

Differential oncogenic potential of geographically distinct Helicobacter pylori CagA isoforms in mice

Abstract: BACKGROUND: The value of local treatment in patients with primary, disseminated, multifocal Ewing sarcoma (PDMES) was investigated. METHODS: We analyzed 120 patients registered into the European Ewing Tumor Working Initiative of National Groups (EURO‐E.W.I.N.G. 99) trial at the trial center of Muenster from 1998 to 2006. Median age was 16.2 years. Local treatment of the primary tumor was surgery in 26 of 120 patients, surgery and radiotherapy in 21 patients, and definitive radiotherapy in 40 patients. For trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 71 publications
5
49
1
1
Order By: Relevance
“…The above observations support the hypothesis that specific TPM patterns could determine the carcinogenic potential of H. pylori isolates, and partly explaining the geographic differences in GC incidence (1). In fact, very recently CagA have been recognized as the first bacterial oncoprotein which acts in mammalian cells (19) and its carcinogenic activity is modulated by specific TPM patterns (20). Therefore, accurate detection of the EPIYA pattern may become a useful prognostic tool for gastric malignancy due to H. pylori infection.…”
supporting
confidence: 66%
“…The above observations support the hypothesis that specific TPM patterns could determine the carcinogenic potential of H. pylori isolates, and partly explaining the geographic differences in GC incidence (1). In fact, very recently CagA have been recognized as the first bacterial oncoprotein which acts in mammalian cells (19) and its carcinogenic activity is modulated by specific TPM patterns (20). Therefore, accurate detection of the EPIYA pattern may become a useful prognostic tool for gastric malignancy due to H. pylori infection.…”
supporting
confidence: 66%
“…pylori strains exhibits a higher oncogenic potential than from western strains, which was attributed to the highly polymorphic EPIYA sequences in the C-terminal region. [38][39][40] From our point of view, the discovery of the CagA 1-200 membrane-binding domain with its inhibitory effect on CagA-induced host cell signaling will add to our understanding of CagA's role as a bacterial protein and of H. pylori induced gastric diseases.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Many of the alterations caused by CagA are associated with malignant transformation of cells (2, 8, 11, 27-29, 33, 49, 54, 56). CagA expression in a transgenic mouse model leads to the development of tumors, and CagA is required for H. pylori-induced gastric carcinoma in a Mongolian gerbil model (23,38,43). Therefore, CagA is considered to be a bacterial oncoprotein (26).…”
mentioning
confidence: 99%
“…1) (27,28,30). Several studies have shown that H. pylori strains with an East Asian form of CagA (EPIYA-D) are associated with an increased risk of gastric cancer compared to strains with a Western form of CagA (EPIYA-C) (3,6,30,32,38,40).…”
mentioning
confidence: 99%